PENERAPAN ASAS - ASAS HUKUM ADAT DALAM PEMBANGUNAN INFRASTRUKTUR YANG BERKEADILAN - Tahegga Primananda Alfath; Ihwan Nul Padli (Arena Hukum, 2021)
Infrastructure Development is one of Indonesia's visions in 2045. However, Infrastructure development has only occurred in some areas, and implementation often occurs in disputes between authorities and indigenous peoples, especially indigenous peoples ulayat rights. The object of ulayat rights is land of the indigenous peoples where its existence is still recognized in Indonesia based on article 18B paragraph (2) of the 1945 Constitution. The research method used statue approach and conseptual approach. This study aims To find out and analyze the existence of indigenous peoples ulayat rights and To know and analyze infrastructure development in Indonesia in accordance with the principles of indigenous peoples, Infrastructure development has the concept of development with the principles of togetherness, based on justice. The State guarantees that infrastructure development in Indonesia is accordance with the principles of indigenous peoples and the principles of indigenous peoples law including the principle of mutual cooperation, the principle of social function in the community, the principle of agreement or consensus and the principle of representation embodied in Article 18B paragraph (2) of the 1945 Constitution and Article 33 paragraph (3) of the 1945 Constitution.